Islamic law : a very short introduction - Baderin, Mashood A. (Oxford : Oxford University Press, 2021)
Islamic law is one of the major legal systems in the world today, yet it is often misunderstood, particularly in the West. This book provides a critical overview of the theory, scope, and practice of Islamic law, taking into account both classical and modern scholarly perspectives in examining the various facets of this key legal system.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 2, 2021).
Keywords: Islamic law